An Empirical Investigation of the Determinants of Foreign Exchange in Nigeria. - Williams, Harley Tega; Sola, Afolabi Taofeek (Archives of Business Research, 2018)
Determinants of capital adequacy ratio (CAR) in the Nigeria banking subsector was carried out using a panel data of 2010 to 2016 from selected commercial banks in Nigeria. A panel data model was specify to show the relationship between Capital Adequacy Ratio and some variables likely to be the determinants of CAR. Thus, this study examines the relationship between capital adequacy ratio and firm specific (deposits, net interest margin, commercial banks branches, return on asset, inflation and exchange rate. In order to investigate these issues a quantitative method research approach was utilized, by using documentary analysis. The study used panel data functional relationship technique to analyze the data. From the study, the regression result shows a positive relationship of 1.8900 on DP and CAR. The test of hypothesis stated in chapter four and the regression results, the findings show net interest margin with a P-value of -2.51. This however, was compared a confidence interval of 5%. -2.51<0.05 we reject the null and accept the alternative hypothesis that there is a significant relationship between net interest margin and capital adequacy ratio. The same procedure was carried out for other variables stated in the study. The implication of this result is that capital adequacy tends to depend on some of this variables. Therefore, a well-functioning banking system contribute in stabilizing inflation and exchange rate. Also a well-functioning bank encourages technological innovation by identifying and funding entrepreneurs with the best chances of successful innovation. This suggestion emerges from the idea that economic growth requires investment and for realisation of investment, capital is necessary.